Charge Carrier Mobility of Alkali Silicate Glasses Calculated by Molecular Dynamics - Welch, Rebecca S.; Wilkinson, Collin James; Mauro, John Christopher; Bragatto, Caio Barca (Frontiers in Materials, 2019)
Ionic conductivity is a property of rapidly increasing interest. Various models attempting to explain ionic conductivity of glass systems have shown limited agreement with experimental results; however, none have been comprehensive. By using molecular dynamics simulations, the diffusion of ion species through a network can be directly observed, providing insights into the mechanisms and their relation to ionic conductivity models. In this report, a method of utilizing molecular dynamics simulations is proposed for the study of the ionic mobility of Na, Li, and K ions in binary silicate glasses. Values found for glasses with x = 0.1, x = 0.2, and x = 0.3 alkali content are between 10-5 and 10-4 cm2·s-1·V-1 and did not change significantly with composition or temperature. This is in agreement with the interstitial pair and weak-electrolyte models used to explain ionic conductivity in glasses.